Determinación del riesgo agroclimático futuro de la zona norte de la Provincia de Los Ríos - Morante Galarza, Yamilet Isamar (2023)
The agroclimatic risk is established by the relationship of the probable climatic affectation, determined by the parameters of precipitation and temperature, on the crops, whose vulnerability is represented by the susceptibility of the crop in its different development cycles and the ability to face adversities due to the management practices of the farmer, the objective of the study was to determine the future agroclimatic risk of the northern zone of the Los Ríos province. Future climate threats were estimated through the Wordclim repository using the MIROC-ES2L model, for the periods 2020-2040, under the Shared Socioeconomic Trajectory (SSP) of climate change, using precipitation and maximum and minimum temperatures, the evapotranspiration with the Thornthwaite method, subsequently a measure of agroclimatic adaptation was designed. The results showed that the increase in precipitation, temperatures and distribution of extreme weather events, such as droughts and heavy rains, will negatively affect agricultural production in the coming years. This project seeks to solve the need to identify and evaluate agroclimatic irrigation to help farmers and adopt preventive measures that can reduce the negative effects of climate changes on their crops. Key words: Agroclimatic Risk, Evapotranspiration, Shared Socioeconomic Trajectories